Conservative treatment of eminentia intercondylaris fractures of the tibia in children - Atay, Ö. Ahmet; Doral, Mahmut Nedim; Tetik, Onur; Leblebicioğlu, Gürsel (The Turkish Journal of Pediatrics, 2002)
Seventeen patients (16 children, 1 adolescent) were reviewed 31 months to 71 months after sustaining the common childhood fracture of the eminentia intercondylaris of the tibia. The aim was to assess long-term results and prognosis by clinical and radiological examination and to discover whether conservative treatment was adequate for type I and type II fractures according to Meyers and McKeever. Early improvement occurred in all patients after conservative treatment, but long-term results were not satisfactory in displaced fractures, which were treated with closed reduction and immobilization in extension. Therefore, anatomic reduction and rigid fixation should be obtained for displaced fractures of the eminentia intercondylaris of the tibia.